Career Aspirations of Geography Teachers – Motives and Self-Perception by Contrast with Students of Other Subjects - Saalfrank, Wolf-Thorsten; Weiß, Sabine; Schramm, Simone; Kiel, Ewald (Journal of Geography Education, 2013)
Prospective geography teachers differ in their career choice motivation from other teacher students. The sample, part of a research project on efficacy and improvement in teacher education at the LMU, has the desire for a job affected by teamwork. The social impact of the future job is also an important motivation. Extrinsic motives like job security are important. Subject-related and pedagogical motives are comparable with all other students. Differentiation by type of school shows, for example, a pedagogical orientation of the motif structure for primary school teachers. Consequences for teacher education as well as development tasks for teacher students were discussed.
Keywords: Teacher education, geography teacher, career choice motivation, study motivation, self-perception, competencies